2012
DOI: 10.1093/toxsci/kfs167
|View full text |Cite
|
Sign up to set email alerts
|

Human and Rat ABC Transporter Efflux of Bisphenol A and Bisphenol A Glucuronide: Interspecies Comparison and Implications for Pharmacokinetic Assessment

Abstract: Significant interspecies differences exist between human and rodent with respect to absorption, distribution, and excretion of bisphenol A (BPA) and its primary metabolite, BPA-glucuronide (BPA-G). ATP-Binding Cassette (ABC) transporter enzymes play important roles in these physiological processes, and their enzyme localization (apical vs. basolateral) in the plasma membrane allows for different cellular efflux pathways. In this study, we utilized an ATPase assay to evaluate BPA and BPA-G as potential substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 40 publications
0
45
0
Order By: Relevance
“…Although it may be that pemetrexed is an obligatory substrate for human MRP2, there have been instances of differential specificity between species, and total hepatic levels of MRP2/Mrp2 protein as well (Li et al, 2009). For instance, bisphenol-A glucuronide has distinct profiles in rodents and humans (Mazur et al, 2012). There are, however, precedents for Mrp2/Mrp3 studies of NASH completed in rodent MCD models that correlate to the human condition more reliably.…”
Section: Mrp2 Facilitates Biliary Elimination Of Pemetrexedmentioning
confidence: 99%
“…Although it may be that pemetrexed is an obligatory substrate for human MRP2, there have been instances of differential specificity between species, and total hepatic levels of MRP2/Mrp2 protein as well (Li et al, 2009). For instance, bisphenol-A glucuronide has distinct profiles in rodents and humans (Mazur et al, 2012). There are, however, precedents for Mrp2/Mrp3 studies of NASH completed in rodent MCD models that correlate to the human condition more reliably.…”
Section: Mrp2 Facilitates Biliary Elimination Of Pemetrexedmentioning
confidence: 99%
“…Though the results obtained with topotecan might indicate a difference in the topotecan transport activity of mouse Bcrp versus human BCRP (see above), the systematic analysis of species differences by using the hBCRP mice is beyond the scope of this work and will be subject to further investigations. On the basis of previously published work, fumitremorgin C could be considered as a potential inhibitor (Gonzalez-Lobato et al, 2010) and pheophorbide A or bisphenol A as substrates (Li et al, 2008;Mazur et al, 2012) for such studies. Thus, the hBCRP mouse model provides a novel tool for identifying differences in inhibitor or substrate interactions with this transporter, either for basic research purposes or in drug development.…”
Section: Discussionmentioning
confidence: 99%
“…While most investigations have focused on the differences in the BCRP expression level between animals and man (Lai, 2009;Li et al, 2009;Warren et al, 2009;Uchida et al, 2011;Chu et al, 2013), a few studies have also reported species differences in BCRP substrate specificity or interaction with inhibitors (Li et al, 2008;Gonzalez-Lobato et al, 2010;Mazur et al, 2012). Although the amino-acid sequences between mouse Bcrp and human BCRP are 81% identical and 86% homologous and therefore relatively conserved (Doyle and Ross, 2003), these proteins vary in more than 90 amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the difference in results between rat and human in the first place can be explained by a species difference in the amino acid sequence of the transporter. It was found that human MRP2 has 78% amino acid sequence identity with rat Mrp2 (Mazur et al, 2012). Moreover, a species difference in Mrp2/MRP2-mediated transport has been shown by several research teams.…”
Section: The Effect Of Hiv Protease Inhibitors On the Bei Of Cdf In Smentioning
confidence: 99%